Implementasi Metode Diskusi Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) Kelas X MAN 5 Kediri - Iqlima Zahari (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
The term implementation is usually associated with an activity, which is carried out to achieve certain goals. Discussion is a group activity of a group of students, talking to each other, exchanging information and opinions about a topic or problem, where each child wants to find answers / solutions to problems from all existing aspects and possibilities. Learning motivation is "the overall driving force within the student that provides direction to learning activities, so that the goals desired by the learning subject can be achieved. Motivation to learn in a person will create passion and enthusiasm for learning, and make a person interested in learning, so that they will want to learn continuously. The history of Islamic culture is a science that studies the work, tastes and creations of Muslim people in the past in social, cultural, economic, political and other forms of life. MAN 5 Kediri is the youngest MAN in Kediri Regency, East Java. Officially founded in 2009 under the name MAN Kandat. The aim of this research is to find out how the discussion method is implemented in SKI subjects at MAN 5 Kediri where SKI lessons are less popular with students because they are seen as complementary subjects. The focus of this research is class X MAN 5 Kediri. This research is field research with a descriptive qualitative approach. Observation, interview and documentation collection techniques. Data analysis techniques include data reduction, data presentation and drawing conclusions/verification. The results of the research show that the discussion method using the syndicate group method in the Islamic Cultural History (SKI) class . However, the weakness is that it is less motivating for students in social studies classes 2, 3, 4 because from the initial screening, these children are also lacking in interest, academics and IQ. The majority of them come from families with poor economic conditions, children from broken homes and children who lack parental attention